[Afisz. Incipit] Koncert Chóru "Cantabile" ... (Gdańsk : [wydawca nieznany], 1966)
Afisz informujący o koncercie w auli Politechniki Gdańskiej 24.08.1966 r.
Keywords: Politechnika Gdańska -- 1945-1990 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.